APLIKASI PEWARNAAN GRAF PADA MASALAH PENYUSUNAN JADWAL PERKULIAHAN DI UNIVERSITAS KUNINGAN - Daswa Daswa; Mohamad Riyadi (Department of Mathematics Education, Universitas Kuningan, 2017)
AbstractAt the beginning of the semester, the study program must arrange a lecture schedule. Among the problems faced is when there are students who take courses at once in one semester. By identifying the course as a knot, the schedule arrangement can be overcome by dyeing the vertex of the graph, by applying the Welch-Powell algorithm. Graph coloring results are neighboring nodes given different colors. With this method can be determined lecture schedule so that no clashing occurs. And courses that can be done simultaneously, that is, the node with the same color.Keywords: Lecture Schedule, Graf Staining, Welch-Powell Algorithm